A Paradigmatic Transition in the General Economic Theory (for the Conditions of Bulgaria) - Todorov, Vasil (Research Papers, 2024)
From the criticisms and discussions lasting decades, and from the correlation of the theory with the reality, a conclusion follows: the neoliberal neoclassical is at variance with the reality, it is inadequate to it. This is increasingly being realized, not only in academia, but also outside of it, and as a result, there is a large-scale loss of confidence in neoliberal neoclassicism and its qualities as a theory for the real economy. In this context, it is necessary to make a paradigm shift in general economic theory, to a new paradigm that will limit or overcome the dominance of the neoliberal neoclassical paradigm. The transition begins. It is less pronounced in the Anglo-Saxon world (USA, Great Britain) and more noticeable in Continental Europe (in Germany, France, Russia, Austria). The key word in it is „pluralism“: replacing the monopolistic dominance of one theory (neoliberal neoclassicism) with a pluralistic body of knowledge (in which neoclassicism will also participate).
Keywords: Paradigm; Paradigm shift; General economic theory